The Evaluation of learning management system in medical education in time of COVID-19: Evaluation of Learning Management System - Kolcu, Giray; Başer Kolcu, Mukadder İnci and Demir, Sadettin and Gülle, Kanat (Progress in Nutrition, 2020)
Study Objectives: Learning management systems (LMS) are the most popular educational technology system used in distance education. In our study, it was aimed to evaluate the acceptance levels of Süleyman Demirel University Faculty of Medicine students regarding the learning management system. Methods: Learning management system acceptance scale (LMSAS) developed by Sezer was preferred for the study. The scale was delivered to all students online, 941 students expressed their opinions (n: 941). Results: In the analysis of scale scores for all students, performance expectation for students is 22.70 ± 9.48, effort expectation is 15.50 ± 5.79, facilitating situations 14.92 ± 5.61, social impact 6.70 ± 3.37 and total score. It was measured as 59.84 ± 21.61. In comparing the preclinic and clinic years, it was seen that there was a statistically significant difference between the preclinical students and the clinical students in both total scores and all subdimensions. Conclusion: In the analysis of scale scores for all students, performance expectation, effort expectation, facilitating situations, social impact and total score are evaluated at the “medium” level for our students. As a result, we believe that the addition of informative and awareness-raising activities related to the LMS within the education program will increase the students’ intention to use a technological innovation in order to improve the acceptance level of the pre-graduate medical education program of the Suleyman Demirel University Faculty of Medicine, which has started the distance education process during the COVID-19 pandemic.